2021
DOI: 10.1016/j.xops.2021.100060
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Automatic Detection of Ellipsoid Zone Loss in Spectral-Domain OCT for Hydroxychloroquine Retinal Toxicity Screening

Abstract: Purpose: Retinal toxicity resulting from hydroxychloroquine use manifests photoreceptor loss and disruption of the ellipsoid zone (EZ) reflectivity band detectable on spectral-domain (SD) OCT imaging. This study investigated whether an automatic deep learning-based algorithm can detect and quantitate EZ loss on SD OCT images with an accuracy comparable with that of human annotations.Design: Retrospective analysis of data acquired in a prospective, single-center, case-control study.Participants: Eighty-five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Additionally, the current method retained this high performance across different device types (i.e., Cirrus and Spectralis devices), whereas the previous reports are limited to only one device type [ 33 , 34 ]. The pixel-wise segmentation accuracy of EZ At-Risk regions of 90% described in the current report is in line with the previous reports from other diseases [ 29 , 30 , 31 ]. Another important distinction from previously reported methods is the exclusion of regions with EZ loss in areas of pre-existing GA from the model training and analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the current method retained this high performance across different device types (i.e., Cirrus and Spectralis devices), whereas the previous reports are limited to only one device type [ 33 , 34 ]. The pixel-wise segmentation accuracy of EZ At-Risk regions of 90% described in the current report is in line with the previous reports from other diseases [ 29 , 30 , 31 ]. Another important distinction from previously reported methods is the exclusion of regions with EZ loss in areas of pre-existing GA from the model training and analysis.…”
Section: Discussionsupporting
confidence: 92%
“…This pipeline had an accuracy of 85% with a sensitivity of 85% and specificity of 85% [ 28 ]. Another automatic DL-based quantification algorithm was used to detect EZ loss in 85 hydroxychloroquine retinopathy patients with an overall accuracy of 90% [ 29 ]. Similarly, automated EZ integrity loss detection in mild diabetic retinopathy achieved an accuracy of 90% in a small cohort of 13 patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Automatic algorithms have been developed to analyze the EZ on SD-OCT images from a variety of retinal diseases. [8][9][10][11][12][13][14][15][16][17][18][19][20] Although most of these algorithms were developed for a specific condition, generalizability is an important aspect of clinical applicability whereby the algorithm can be applied to other conditions. Trainable algorithms, such as modern deep learning-based algorithms, have especially strong potential to do so, given the appropriate training dataset.…”
mentioning
confidence: 99%
“…Studies have already demonstrated promising data on machinelearning models that incorporate clinical and/or structural quantitative data in detecting toxicity and predicting those at risk of progression. 43,44 Eventually, raw functional and structural data can be used, minimizing reliance on scan quality and leading to the identification of new imaging biomarkers for early toxicity which could provide novel insights into the mechanism of HCQ toxicity. '…”
Section: Nuances In Clinical Testingmentioning
confidence: 99%